Genome-Wide DNA Methylome and Transcriptome Analysis of Porcine Testicular Cells Infected With Transmissible Gastroenteritis Virus - Wu, Jiayun; Shi, Xiaoru; Wu, Lisi; Wu, Zhengchang; Wu, Shenglong; Bao, Wenbin (Frontiers in Veterinary Science, 2022)
Transmissible gastroenteritis virus (TGEV) is a porcine pathogen causing highly communicable gastrointestinal infection that are lethal for suckling piglets. In an attempt to delineate the pathogenic mechanism of TGEV-infected porcine testicular cells (ST cells), we conducted a whole genome analysis of DNA methylation and expression in ST cells through reduced bisulfate-seq and RNA-seq. We examined alterations in the methylation patterns and recognized 1764 distinct methylation sites. 385 differentially expressed genes (DEGs) were enriched in the viral defense and ribosome biogenesis pathways. Integrative analysis identified two crucial genes (EMILIN2, RIPOR3), these two genes expression were negatively correlated to promoter methylation. In conclusion, alterations in DNA methylation and differential expression of genes reveal that their potential functional interactions in TGEV infection. Our data highlights the epigenetic and transcriptomic landscapes in TGEV-infected ST cells and provides a reliable dataset for screening TGEV resistance genes and genetic markers.